Pengaruh Flexing Terhadap Perilaku Mahasiswa Dalam Belanja Online Melalui Tiktok Dengan Aspek Prudential Sebagai Variabel Moderasi: Studi Kasus Mahasiswa IAI Hamzanwadi Pancor - Aulia Fitri; Zainul Hasan Quthbi; Yuyun Andriani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the effect of flexing on students’ online shopping behavior through the TikTok platform, with the prudential aspect as a moderating variable. The flexing phenomenon on social media has triggered consumerist behavior, especially among students who are active on digital platforms. This research employs a quantitative approach using multiple linear regression analysis. The population consists of students from IAI Hamzanwadi Pancor, selected through a purposive sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using normality tests, t-tests, and the coefficient of determination (R²). The findings reveal that flexing has no significant effect on students’ online shopping behavior through TikTok, while the prudential aspect shows a positive and significant influence. This indicates that students’ consumer behavior is more controlled by prudential considerations than by lifestyle displays on social media. Therefore, enhancing financial literacy and developing responsible shopping awareness are essential in shaping rational consumption behavior in the digital era.